Pharmacokinetics of zanamivir in critically ill patients undergoing continuous venovenous hemofiltration. Issue 1 (7th January 2023) - Wieringa, André; ter Horst, Peter GJ; Wagenvoort, GertJan HJ; Koch, Birgit CP; Haringman, Jasper J
Background: Limited data exist for dosing of zanamivir in the setting of CVVH in the intensive care unit (ICU). Our objective is to report the pharmacokinetics and sieving coefficient (Sv ) of zanamivir in patients receiving continuous venovenous hemofiltration (CVVH). Methods: In this prospective observational study, patients of ≥18 years admitted to the ICU with a life-threatening Influenza A or B infection, treated with zanamivir i.v. undergoing CVVH were included. Patients received a zanamivir loading dose of 600 mg i.v., 12 h later followed by maintenance dosages two times daily according to the treating physician. Per patient, nine CFT plasma and nine ultrafiltrate samples were drawn on day 2 of treatment and analysed with a validated HPLC-MS/MS method. Results: Four patients were included in the study. The zanamivir elimination half-life was prolonged with 5.6–9.9 h, compared to patients with normal renal function. A Sv of approximately 1.0 was identified, with unrestricted transport of zanamivir to the ultrafiltrate. Conclusions: Zanamivir is well cleared by CVVH. In absence of the possibility for therapeutic drug monitoring, the ultrafiltration rate seems as a good surrogate parameter to estimate the CLCVVH and may help guide the dosing of zanamivir.